Synthesis and structure of (E)-3,4,5-trihydroxy-N′-(3,4,5-trimethoxybenzylidene)benzohydrazide monohydrate - Mamadou Lo; Bineta Sene; Adji Fatou Fall Pouye; Arie van der Lee; Abdoulaye Gassama; Sébastien Richeter (Acta Crystallographica Section E: Crystallographic Communications)
In the structure of the title compound, C17H18N2O7·H2O, hydrogen bonds link three molecules to the water molecule. Additional hydrogen-bonding interactions connect two molecules via the amide nitrogen donor and two methoxy oxygen acceptors. This three-dimensional hydrogen-bond network has no particular directionality, and a slight disorder of two methoxy groups is observed. According to force-field calculations, weaker but more extended van der Waals interactions show a larger stabilization effect than the hydrogen-bond interactions, while hydrogen-bond analysis suggests that polymorphs of the compound may be found in the future.